The Effect of Green Friendliness on Green Trust: The Roles of Green Satisfaction and Green Perceived Quality among Wardah Skincare Consumers - Putri Yusniya Wulan Agustin; Budi Sutiono Pratama Nugraha (JURNAL ECONOMINA, 2026)
This study examines the effect of Green Friendliness on Green Trust and assesses the roles of Green Satisfaction and Green Perceived Quality among Wardah skincare consumers. The study applied a quantitative explanatory survey with a cross-sectional design. Data were collected through an online questionnaire. Convenience-based recruitment was followed by purposive screening, yielding 157 valid respondents. The proposed relationships were analysed using partial least squares structural equation modelling (PLS-SEM) with SmartPLS. The findings show that Green Friendliness has positive and significant effects on Green Satisfaction and Green Perceived Quality. However, its direct effect on Green Trust is not statistically significant. Green Satisfaction and Green Perceived Quality each have positive and significant effects on Green Trust. The model explains 76.4% of the variance in Green Trust (R² = 0.764). These findings indicate that consumers’ Green Trust is more closely associated with their evaluations of green product quality and their green satisfaction than with Green Friendliness alone.